Answer:
Answer: Third option is the right answer.
Step-by-step explanation:
First we the write the expression
![(a+b)(a^{2}+b^{2}-ab)](https://tex.z-dn.net/?f=%28a%2Bb%29%28a%5E%7B2%7D%2Bb%5E%7B2%7D-ab%29)
Now teacher says that the product of these polynomials will result in the sum of ![a^{3}+b^{3}](https://tex.z-dn.net/?f=a%5E%7B3%7D%2Bb%5E%7B3%7D)
Now the teacher ask if we put the value of a = 2x and b = 1 then what will be the expression look like.
![(2x+1)\left [ (2x)^{2}+(1^{2})-(2x)(1)\right ]](https://tex.z-dn.net/?f=%282x%2B1%29%5Cleft%20%5B%20%282x%29%5E%7B2%7D%2B%281%5E%7B2%7D%29-%282x%29%281%29%5Cright%20%5D)
=![(2x+1)(4x^{2}+1-2x)](https://tex.z-dn.net/?f=%282x%2B1%29%284x%5E%7B2%7D%2B1-2x%29)
So third option is looking like our expression.
I can’t seem to look at the bottom two answers and the two ( A and B) are not correct. So you’re left with either C or D
Answer:
-18
Step-by-step explanation:
Left Hand Side = -2(7a + 9b) = -14a - 18b
Comparing it with Right Hand Side, ? = -18
1.3 million stocks was there in beginning of the day
Answer:
plz ion know what is the awnser to mine
Step-by-step explanation: